Kazantzakis Creator of the Odyssey and Reader of Homer: Terms of Reception and Euro-American Mediations - Ζερβού Αλεξάνδρα (Education Sciences, 2019)
The study focuses on Kazantzakis’s perception of the Homeric myth, as well as on the perception of his own Odyssey by the reading public outside Greece. Kazantzakis studied the Homeric text and reflected on the Homeric epic with the help and mediation of the French translation of it by Victor Bérard, as well as of the dramatic version in German, Der Bogen des Odysseus, by G. Hauptmann. He was working on the creation of his own Odyssey during the long period in which Homeric research was dominated by the Unitists and the Neoanalytical School, headed by I.Th. Kakridis, future collaborator of the Cretan author on the translation of Homer. So, Kazantzakis felt he was justified in conversing with the great, one of a kind ancestral poet and in considering that his own personal creation is made in the image of the Homeric one, in the framework of an attitude which we would call complaisance narcissique. The special familiarity and affinity that Kazantzakis felt with the ancestral poet enabled him to continue his own work and even to proceed to a parodying reversal of typical Homeric passages, such as the genealogies. His self-portrait Odysseus is a flâneur, in the metaphorical and literal sense of the term, because he loves wandering in different geographical regions, cultures and ideologies. This anarchic and tolerant ideological diversity, together with the concept of the everlasting journey, made Kazantzakis’s Odyssey a popular book and a best-seller for the Hippy and the Beat generation, with the mediation, of course, of the simplifying and easily readable English translation by Kimon Friar. In general, the perception of Kazantzakis’s Odyssey takes place in comparison and conflict with other Homeric transcripts, and indeed with James Joyce’s Ulysses, a work that appears to handle the myth in a diametrically opposite manner.